1958
DOI: 10.1111/j.1440-1819.1958.tb00623.x
|View full text |Cite
|
Sign up to set email alerts
|

Familtal Paralysis Agitans Juvenilis. A Clinical, Anatomical and Genetic Study

Abstract: Summary Three familial cases of juvenile type of paralysis agitans have been reported with the following results H A parkinsonian syndrom not due to a latcrit encephalitis can develop before 20 years of age. 2) Its clinical and anatomical findings are very similar to that of classical paralysis agitans. 3) By a detailed genetic study it is demonstrated that the disease is inherited in a recessive mode. The author's heartfelt thanks are due to Prof. Mitsuda, Prof. Yoshida, and Dr. Kawai for their kind advice in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0
3

Year Published

1977
1977
2000
2000

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 6 publications
0
10
0
3
Order By: Relevance
“…This is all the more the case, if childhood and juvenile patients are included in the analysis (Yokochi and Narabayashi, 1981). Familial YOPD may (Yokochi and Narabayashi, 1981;Muenter et al, 1986Muenter et al, , 1994Quinn et al, 1987) and may not (Ota et al, 1958;Mata et al, 1983;Mayer et al, 1986;Dwork et al, 1993;Takahashi et al, 1994) be characterized in terms of typical nerve cell loss with Lewy body (LB) formation in the substantia nigra and elsewhere in the brain. With LB pathology, familial YOPD has been found to occur with clinically atypical features such as dystonia (Yokochi and Narabayashi, 1981) and with early dementia (Muenter et al, 1986(Muenter et al, , 1994.…”
Section: The Diagnostic and Nosologic Significance Of Tremor In Familmentioning
confidence: 97%
See 1 more Smart Citation
“…This is all the more the case, if childhood and juvenile patients are included in the analysis (Yokochi and Narabayashi, 1981). Familial YOPD may (Yokochi and Narabayashi, 1981;Muenter et al, 1986Muenter et al, , 1994Quinn et al, 1987) and may not (Ota et al, 1958;Mata et al, 1983;Mayer et al, 1986;Dwork et al, 1993;Takahashi et al, 1994) be characterized in terms of typical nerve cell loss with Lewy body (LB) formation in the substantia nigra and elsewhere in the brain. With LB pathology, familial YOPD has been found to occur with clinically atypical features such as dystonia (Yokochi and Narabayashi, 1981) and with early dementia (Muenter et al, 1986(Muenter et al, , 1994.…”
Section: The Diagnostic and Nosologic Significance Of Tremor In Familmentioning
confidence: 97%
“…Without LB features, mere parkinsonism has been described, but dystonia (Dwork et al, 1993;Takahashi et al, 1994) and dementia (Mata et al, 1983) were also observed. The possible modes of inheritance in families, where LB pathology was not present, were varying, too (autosomal-recessive: Ota et al, 1958;Mata et al, 1983;Takahashi et al, 1994;autosomal-dominant: Mata et al, 1983;Mayer et al, 1986;Dwork et al, 1993).…”
Section: The Diagnostic and Nosologic Significance Of Tremor In Familmentioning
confidence: 97%
“…6 There is also a juvenile form of parkinsonism which shows a clear autosomal recessive mode of transmission. 36 More recently, two large kindreds were reported 7 with evidence of a single gene action modulated by environmental factors affecting duration of the disease. All these studies suggest some degree of genetic influence in one or more pedigrees.…”
Section: Genetic Factorsmentioning
confidence: 99%
“…Outros casos familiares foram apresentados em 19S8, quando Ota et al 47 , relataram uma família com três irmãos (2 irmãs e 1 irmão) que iniciaram um parkinsonismo juvenil aos 12, 13 e aos 20 anos. Uma das pacientes, faleceu aos 49 anos e seu cérebro foi estudado patologicamente.…”
unclassified
“…Além das alterações palidais anteriormente descritas, Davison encontrou alterações na substância negra, além de desmielinização dos feixes corticoespinhais, o que o levou a denominar seus casos (havia mais 4 com sinais piramidais que não foram estudados patologicamente) de "doença pálido-piramidal". Em 1958, Ota et al 47 , apresentaram a primeira descrição de estudo patológico com alterações semelhantes às habitualmente vistas nos casos clássicos de DP, com despigmentação da substância negra, perda neuronal em vários núcleos da base, locus ceruleus e também perda neuronal na camada granular do cerebelo. Não fizeram menção ao encontro de corpúsculos de Lewy na substância negra.…”
unclassified